LC–MS/MS and chiroptical spectroscopic analyses of multidimensional metabolic systems of chiral thalidomide and its derivatives. Issue 6 (19th April 2017) - Ogino, Yoshiyuki; Tanaka, Masahito; Shimozawa, Togo; Asahi, Toru
Abstract: Enantiomeric thalidomide undergoes various kinds of biotransformations including chiral inversion, hydrolysis, and enzymatic oxidation, which results in several metabolites, thereby adding to the complexity in the understanding of the nature of thalidomide. To decipher this complexity, we analyzed the multidimensional metabolic reaction networks of thalidomide and related molecules in vitro . Characteristic patterns in the amount of various metabolites of thalidomide and related molecules generated during a combination of chiral inversion, hydrolysis, and hydroxylation were observed using liquid chromatography–tandem mass spectrometry and chiroptical spectroscopy. We found that monosubstituted thalidomide derivatives exhibited different time‐dependent metabolic patterns compared with thalidomide. We also revealed that monohydrolyzed and monohydroxylated metabolites of thalidomide were likely to generate mainly by a C‐5 oxidation of thalidomide and subsequent ring opening of the hydroxylated metabolite. Since chirality was conserved in most of these metabolites during metabolism, they had the same chirality as that of nonmetabolized thalidomide. Our findings will contribute toward understanding the significant pharmacological effects of the multiple metabolites of thalidomide and its derivatives. Abstract :